2021
DOI: 10.3390/cells11010057
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Triggers CRAC-Dependent Calcium Influx and Apoptosis through the Recruitment of Autophagy Proteins to Death-Inducing Signaling Complex

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) selectively kills various cancer cell types, but also leads to the activation of signaling pathways that favor resistance to cell death. Here, we investigated the as yet unknown roles of calcium signaling and autophagy regulatory proteins during TRAIL-induced cell death in leukemia cells. Taking advantage of the Gene Expression Profiling Interactive Analysis (GEPIA) project, we first found that leukemia patients present a unique TRAIL receptor gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Notably, expression of GABBR1 ( gamma aminobutyric acid type B receptor 1 ), which our group has recently shown to oppose CaSR-mediated calcium sensing in the parathyroid ( 34 ), is significantly elevated in Def-Ts. Additional genes found to be significantly upregulated in these tumors act in signaling pathways controlling apoptosis (TNFSF10, tumor necrosis superfamily member 10 ) ( 35 , 36 ), cellular stress response (SGK1, serum glucocorticoid regulated kinase 1 ) ( 37 ), inositol-derived second messenger production (IPMK, inositol polyphosphate multikinase ) ( 38 ), and energetic metabolism (AMPD3, adenosine monophosphate deaminase 3 ) ( 39 ). Despite the higher preoperative PTH observed in vitamin D-deficient PHPT patients, PTH transcript abundance was not significantly different between tissue sources ( P = 0.2862 by one-way ANOVA) or when comparing chief to oxyphil cells ( P = 0.7284 by unpaired t -test).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, expression of GABBR1 ( gamma aminobutyric acid type B receptor 1 ), which our group has recently shown to oppose CaSR-mediated calcium sensing in the parathyroid ( 34 ), is significantly elevated in Def-Ts. Additional genes found to be significantly upregulated in these tumors act in signaling pathways controlling apoptosis (TNFSF10, tumor necrosis superfamily member 10 ) ( 35 , 36 ), cellular stress response (SGK1, serum glucocorticoid regulated kinase 1 ) ( 37 ), inositol-derived second messenger production (IPMK, inositol polyphosphate multikinase ) ( 38 ), and energetic metabolism (AMPD3, adenosine monophosphate deaminase 3 ) ( 39 ). Despite the higher preoperative PTH observed in vitamin D-deficient PHPT patients, PTH transcript abundance was not significantly different between tissue sources ( P = 0.2862 by one-way ANOVA) or when comparing chief to oxyphil cells ( P = 0.7284 by unpaired t -test).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, both TRAIL- and FasL-induced pro-metastatic pathways are associated with an early increase in intracellular Ca 2+ and tyrosine kinase signalling [ 114 , 415 , 416 ]. The use of isogenic stable cancer cells deficient for either DR4 or DR5 [ 114 ], demonstrated that TRAIL-induced pro-metastatic signalling was solely triggered by DR5 and correlated with a rapid Ca 2+ flux [ 114 , 417 , 418 ]. Furthermore, early increased cytosolic Ca 2+ was shown to be activated upon TRAIL exposure in both Jurkat and NB4 leukemia cells, protecting the latter from apoptosis [ 418 ].…”
Section: Signalling Machinery Associated With Trail Non-canonical Tra...mentioning
confidence: 99%
“…The use of isogenic stable cancer cells deficient for either DR4 or DR5 [ 114 ], demonstrated that TRAIL-induced pro-metastatic signalling was solely triggered by DR5 and correlated with a rapid Ca 2+ flux [ 114 , 417 , 418 ]. Furthermore, early increased cytosolic Ca 2+ was shown to be activated upon TRAIL exposure in both Jurkat and NB4 leukemia cells, protecting the latter from apoptosis [ 418 ]. It was found in these cells that recruitment of both p62 and ATG7 to complex I was required for calcium influx induced by TRAIL [ 418 ].…”
Section: Signalling Machinery Associated With Trail Non-canonical Tra...mentioning
confidence: 99%
See 2 more Smart Citations